Learning analytics for continuous learning-processes improvement through dynamic data-informed decisions - de Waal, Paula (Formazione & insegnamento, 2017)
The Learning Analytics field is an interdisciplinary scenario where the methods of Data Science and Educational Sciences Research are applied to the practices of educational systems at all levels. The point of convergence between the various disciplines involved is the assumption that the new systematic and ubiquitous data collection processes and their progressive modelling can be translated into Insights and Actionable Data with high-impact on educational decision-making, educational problem-solving and continuous improvement of learning processes. The article discusses Learning Analytics issues that could benefit from Pedagogical Research approaches.